Family Medicinal Plants (TOGA) Self-Care as a Non-Pharmacological Therapy for Hypertension Control - Vebi Rizki Aulia; Ning Arti Wulandari; Sandi Alfa Wega Arsa (Dewan Pimpinan Daerah Persatuan Perawat Nasional Indonesia Kota Blitar, 2025)
Hypertension is a non-communicable disease with a high prevalence that can cause serious complications and even death if not treated optimally. To prevent hypertension complications, hypertension control efforts are needed, one of which is with non-pharmacological therapies such as the use of Family Medicinal Plants (TOGA) as a natural alternative in controlling blood pressure. This research aims to increase the knowledge, skills, and independence of the community in managing hypertension through independent care of TOGA, especially in the Tera Gymnastics group in Blitar Village. The implementation of activities included health education, demonstrations, and blood pressure measurements, which were attended by 44 respondents. Evaluation was carried out through pretest and posttest knowledge, as well as blood pressure measurements before and after intervention. The results of the study used the Wilcoxon Signed Rank Test, which showed an increase in knowledge with a value of p < 0.005, which means that there is an influence on the knowledge of partners. In the post-test after being given herbal drinks, a decrease in systolic and diastolic blood pressure was obtained; the average results were that the systolic blood pressure value decreased by 7.95 mmHg and the diastolic by 2.43 mmHg. TOGA Independent Care has proven to be effective as a complementary therapy in efforts to control hypertension. It is hoped that this program can continue and be developed in other communities as a sustainable promotive and preventive effort.